Vídeo educacional como instrumento de aprendizagem da técnica de higiene bucal em pacientes intubados - Silva, Kellyn Patricia da (2020)
Introduction: Ventilator-associated pneumonia (VAP) affects percentage significant impact of patients using invasive mechanical ventilation, promoting adverse effects on and often fatal outcomes resulting from lung injury due to its prolonged use. Oral hygiene is a mediating care and of paramount importance prevention of pneumonia in these patients, but when performed in a manner that is inadequate, the oral cavity becomes a focus of colonization contributing to the development of VAP and consequent increase in patient criticality, expanding the probability of complications. However, discernment on how to perform this technique of is scarce and absent in the training of health professionals, causing them to this care is not often carried out in the appropriate manner or prioritized in the patient care. Information and communication technologies make it possible to training of these professionals in the search for knowledge and improvement in the care provided to the patient. Objective: To develop a learning tool through a video training of health professionals in the proper performance of the hygiene technique patients on mechanical ventilation hospitalized in intensive care units. Method: This is a methodological study of the development of the object of Learning. The proposition for the construction of the video is based on the literature and has been composed of 3 stages: Pre-production, construction of the script, synopsis, argument; Production: preparation of the environment, rehearsal with the actresses, development of the narration, choice of positioning and filming of the scenes; Post-production: editing of the scenes, introduction of images and adjustment of the narration. Results: An educational video was obtained with the offer of a safe tool for health professionals in carrying out the oral hygiene. Seven scenes consisting of images were elaborated together with the from the preparation of the environment to the outcome as the annotation in Chart. Conclusion: The product of this study represents an innovative strategy of training, based on the best scientific evidence, and may direct the actions of the health professionals in performing oral hygiene for critically ill patients using mechanical ventilation, since it allows the acquisition of knowledge and underpins the Assistance.